2022
DOI: 10.3390/pr10091695
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study for Flow Loss Characteristic of an Axial-Flow Pump as Turbine via Entropy Production Analysis

Abstract: Low-head vertical axial-flow pump as turbine (PAT) devices play a vital part in the development of clean energy for hydropower in plain areas. The traditional method of evaluating the flow loss in hydraulic machinery is calculated by the pressure drop method, the limitation of which is that the location of the occurrence of large losses cannot be accurately determined. In this paper, entropy production theory is introduced to evaluate the irreversible losses in the axial-flow PAT from the perspective of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In throttle and bypass control, the recovered power (P rec ) is calculated by using the PAT's power characteristic curve, which can be derived experimentally (as performed in this paper) or by applying one of the methodologies available in the literature. To this purpose, different approaches can be exploited, e.g., physics-based approaches (e.g., [36,37]), empirical models (e.g., [23,38,39]), black box models (e.g., [40,41]), CFD models (e.g., [39,42]) and entropy production analysis (e.g., [43]).…”
Section: Pat Controlmentioning
confidence: 99%
“…In throttle and bypass control, the recovered power (P rec ) is calculated by using the PAT's power characteristic curve, which can be derived experimentally (as performed in this paper) or by applying one of the methodologies available in the literature. To this purpose, different approaches can be exploited, e.g., physics-based approaches (e.g., [36,37]), empirical models (e.g., [23,38,39]), black box models (e.g., [40,41]), CFD models (e.g., [39,42]) and entropy production analysis (e.g., [43]).…”
Section: Pat Controlmentioning
confidence: 99%
“…Just as stated in Kumar's paper [35], under rated conditions, the inlet flow at the draft tube is nearly identical to the normal outflow; however, as the flow rate increases, the strong swirl flow is directed contrary to the runner's rotation, and eventually, a cavitation vortex rope shaped like torch forms. In addition, as shown in the black highlighted area of the figure, the motion of the vortex rope has a significant effect on the flow pattern at the inlet inside the draft tube, forming a high-speed zone and a large-scale vortex structure below the vortex rope [36]. As the load increases, the vortex distribution at the outlet of the draft tube is improved; nevertheless, in the red wireframe area of the figure, the vortex ropes are gradually serious and closer to the elbow section in the Case 3 condition, so the energy loss caused by the vortex ropes inside the draft tube will increase.…”
Section: Analysis Of Internal Flow Fieldmentioning
confidence: 99%
“…The highest pressure value was found in the impeller outlet region. Yang et al [19,20] investigated the energy-loss characteristics of an axial flow pump. Research has shown that the pressure energy loss in the impeller is the largest.…”
Section: Introductionmentioning
confidence: 99%